Gerontologic nursing - Meiner, Sue E.; Yeager, Jennifer J. (St. Louis, Missouri : Elsevier Science, 2019)
This disorder-focused gerontologic nursing text features an enhanced focus on nursing management and care coordination across health care delivery settings. It emphasizes topics such as nutrition, chronic illness, emergency treatment, patient teaching, home care, and end-of-life care -- and includes the latest guidelines for mammograms, colonoscopies, pneumonia, and shingles vaccinations.
Part I: Introduction to Gerontologic Nursing -- 1. Overview of Gerontologic Nursing -- 2. Theories Related to Care of the Older Adult -- 3. Legal and Ethical Issues -- 4. Assessment of the Older Adult -- Part II: Influences on Health and Illness -- 5. Cultural Influences -- 6. Family Influences -- 7. Socioeconomic and Environmental Influences -- 8. Health Promotion and Illness/Disability Prevention -- Part III: Influences on Quality of Life -- 9. Nutrition -- 10. Sleep and Activity -- 11. Safety -- 12. Sexuality and Aging -- 13. Pain -- 14. Infection and Inflammation -- Part IV: Diagnostic Studies and Pharmacologic Management -- 15. Laboratory and Diagnostic Tests -- 16. Drugs and Aging Part V: Nursing Care of Physiologic and Psychologic Disorders -- 17. Integumentary Function -- 18. Sensory Function -- 19. Cardiovascular Function -- 20. Respiratory Function -- 21. Gastrointestinal Function -- 22. Urinary Function -- 23. Musculoskeletal Function -- 24. Cognitive and Neurologic Function -- 25. Endocrine Function -- Part VI: Health Care Transitions -- 26. Health Care Delivery Settings and Older Adults -- 27. Chronic Illness and Rehabilitation -- 28. Cancer -- 29. Loss and End-of-Life Issues.
Includes index.
Keywords: GERIATIC NURSING